Antibacterial high-entropy alloy with low copper content, preparation method and application

The antibacterial high-entropy alloy (LCC-AHEA) with low copper content uses the synergy of multi-elements to achieve efficient antibacterial properties while maintaining the mechanical properties and corrosion resistance of metal materials, solving the problem that traditional antibacterial materials are difficult to coordinate in the mechanical properties, corrosion resistance and antibacterial properties.

CN119710429APending Publication Date: 2025-03-28ZHEJIANG PROVINCIAL PEOPLES HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928955.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional antibacterial materials with high copper content are difficult to take into account both antibacterial properties, mechanical properties and corrosion resistance, and the antibacterial coating is prone to falling off and has high cost.

Method used

The antibacterial high-entropy alloy (LCC-AHEA) with low copper content is used to achieve efficient antibacterial through the synergy of multi-elements and the synergy of Co-led Al, Ni, and Cu plasmas, while maintaining good mechanical properties and corrosion resistance.

Benefits of technology

While achieving efficient antibacterial properties, the mechanical properties and corrosion resistance of metal materials are maintained, solving the problem that traditional antibacterial materials are difficult to coordinate in the mechanical properties, corrosion resistance and antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710429A_ABST
    Figure CN119710429A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial high-entropy alloy with low copper content, a preparation method and application, and belongs to the technical field of metal materials, the chemical formula of the antibacterial high-entropy alloy is AlxCoyCrCuzFeNiSi0.2, x is more than or equal to 0.3 and less than or equal to 0.6, y is more than or equal to 1.0 and less than or equal to 1.5, and z is more than or equal to 0.05 and less than or equal to 0.3; the microstructure of the antibacterial high-entropy alloy is of a two-phase structure and comprises a dendritic phase rich in Cr and Fe and an interdendritic phase rich in Al and Ni. The yield strength of the antibacterial high-entropy alloy is 751 MPa, the limit compressive strain is 40%-42%, and the passivation interval is 0.5 V. The antibacterial high-entropy alloy has excellent corrosion resistance, ions such as Al, Co, Ni and Cu can be dissolved out when the alloy is corroded by bacteria, splitting of the bacteria is inhibited under leading of the Co ions, and the antibacterial rate of 96%-98% on escherichia coli in one day and 100% on escherichia coli in three days is achieved; when no bacterial corrosion exists, a compact oxidation film is rapidly generated on the surface, and release of harmful ions is inhibited. The method has great research value and significance in the aspects of biomedicine, food processing, living home, national important engineering equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to an antibacterial high-entropy alloy with low copper content, a preparation method and application thereof. Background Art

[0002] With the development of biomedical technology, new requirements have been put forward for the antibacterial properties of medical device materials, which has become a hot spot in the research of new materials. Traditional antibacterial materials are made by adding the antibacterial element Cu to the materials, releasing Cu ions during service, and effectively killing bacteria by destroying bacterial cell membranes, inducing oxidative stress reactions, and promoting protein denaturation. However, since the antibacterial property is positively correlated with the Cu content, in order to achieve the ideal antibacterial effect, it is usually necessary to add a higher content of Cu (>wt.%) to the stainless steel matrix. The higher content of Cu elements is easy to segregate at the grain boundaries of the material to form a Cu-rich phase or single Cu, which splits the matrix structure and reduces the ductility of the material. At the same time, it will also form a primary cell in the micro-region, reducing the corrosion resistance of the material. This makes it impossible for Cu-containing alloys to take into account antibacterial properties, mechanical properties and corrosion resistance. The Cu element coating can effectively avoid the damage of the copper-rich phase to the mechanical properties and corrosion resistance of the matrix, but the adhesion of the antibacterial coating to the matrix material is relatively poor, easy to fall off, easy to wear, and cannot achieve long-term self-cleaning and antibacterial. It needs to be replaced every once in a while, which significantly increases the cost. Therefore, these traditional high-copper antibacterial materials have great limitations and cannot strike a balance between antibacterial properties, corrosion resistance and mechanical properties.

[0003] High Entropy Alloy (HEA) is a new type of material with excellent performance. It is composed of more than five main elements, and the atoms of each element randomly occupy a lattice site. The "high entropy" of high entropy alloy refers to chemical disorder or topological disorder at the atomic scale, that is, the atomic arrangement of the alloy is highly disordered and in a disordered state. High entropy alloys can show corrosion resistance comparable to traditional alloys, better mechanical properties and thermal stability. At the same time, the cocktail effect of high entropy alloys (the synergistic effect of multiple elements) leads to the overall performance of the alloy being better than the simple sum of the properties of each component, and even produces an additional effect, showing properties that any one of the pure metals of the elements does not have. However, due to its unique elemental composition, arrangement and interaction potential field, high entropy alloys tend to form a simple disordered solid solution (FCC, BCC or HCP), which inhibits the precipitation of copper-rich phases, but it is still unavoidable when the copper content is too high. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides an antimicrobial high entropy alloy with a low copper content, a preparation method and an application thereof, and utilizes the high entropy effect and cocktail effect of the high entropy alloy to prepare an antimicrobial high entropy alloy with a low copper content (LowCopper Content Antimicrobial High Entropy Alloy, LCC-AHEA for short). The damage to the antimicrobial effect caused by reducing the Cu content is compensated by the synergistic effect of multiple elements, and while obtaining high-efficiency antimicrobial properties, the mechanical properties and corrosion resistance of the metal material are maintained, so as to solve the technical problem that the mechanical properties, corrosion resistance and antimicrobial properties of the existing antimicrobial alloys are difficult to coordinate.

[0005] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides an antibacterial high entropy alloy with a low copper content, wherein the chemical formula of the antibacterial high entropy alloy is Al x Co y CrCu z FeNiSi 0.2 , where 0.3 ≤ x ≤ 0.6, 1.0 ≤ y ≤ 1.5, and 0.05 ≤ z ≤ 0.3.

[0006] Preferably, the microstructure of the antibacterial high entropy alloy is a two-phase structure, including a dendrite phase rich in Cr and Fe, and an interdendritic phase rich in Al and Ni.

[0007] Preferably, the ratio of the dendrite phase to the interdendritic phase is (7 to 8): (2 to 3).

[0008] Preferably, the antibacterial high entropy alloy has a yield strength of 751 MPa, an ultimate compressive strain of 40% to 42%, and a passivation interval of 0.5 V.

[0009] Preferably, a passivation film can be formed on the surface of the antibacterial high entropy alloy, which is destroyed under the conditions of bacterial corrosion and continuously releases Al, Co, Cu, and Ni ions. The released ions synergistically destroy the morphological integrity of bacteria, inhibit bacterial division, and achieve antibacterial properties.

[0010] Preferably, the antibacterial rate of the antibacterial high entropy alloy against Escherichia coli is 96% to 98% in 1 day and 100% in 3 days.

[0011] In a second aspect, the present invention provides a method for preparing an antibacterial high entropy alloy with a low copper content, comprising the following steps: Step 1: Follow Al x Co y CrCu z FeNiSi 0.2 Ingredients: Step 2, subjecting the ingredients of step 1 to multiple vacuum suspension melting in an oxygen-free environment to obtain a high entropy alloy ingot; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

[0012] Preferably, the Al, Co, Cr, Cu, Fe, Ni and Si are all raw materials with a purity of 99.9wt.% or above.

[0013] Preferably, the temperature of the suspension smelting in step 2 is 1900-2100°C.

[0014] Preferably, the vacuum degree is 4 to 6×10 -3 Pa, and then the vacuum chamber is backfilled with high-purity argon gas to 0.03 ~ 0.05MPa to form an oxygen-free melting environment.

[0015] In a third aspect, the present invention provides an antibacterial high entropy alloy with a low copper content for use in the field of antibacterial metal materials.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The copper content in the antibacterial high entropy alloy with low copper content of the present invention is low and evenly distributed in the matrix, which is not enough to precipitate copper-rich phase and elemental copper, and reduces the segregation of Cu element. Secondly, the strength of the antibacterial high entropy alloy is improved by high lattice distortion and high-density phase boundary. The high lattice distortion comes from the different atomic sizes constituting the LCC-AHEA lattice. This lattice distortion introduces high-amplitude sliding resistance, making plastic deformation difficult. And the high-density phase boundary can also directly hinder sliding, so that LCC-AHEA can withstand a higher load than ordinary stainless steel. At the same time, LCC-AHEA fails when the compression engineering strain is about 41%, indicating that it has good plasticity, which is due to the coordinated deformation of the fine two-phase structure. In addition, another notable feature of the LCC-AHEA compression stress-strain curve is that the continuous strain hardening ability is strong, and the hardening rate is close to 5GPa. The reason is that dislocations are accumulated at high-density phase boundaries, which increases the back stress and enables LCC-AHEA to obtain additional strain hardening.

[0017] The antibacterial high entropy alloy with low copper content of the present invention has antibacterial properties derived from the synergistic effect of Al, Ni, Cu and other ions led by Co, which replaces the high-content Cu element to achieve high-efficiency antibacterial properties. The microbial corrosion of Escherichia coli destroys the dense oxide film on the surface of the alloy and releases Al, Co, Cu, Ni and other ions; these ions destroy the integrity of the Escherichia coli cell structure, interfere with its DNA replication and RNA transcription, and inhibit its division; after the death of Escherichia coli, the surface of the alloy is rapidly passivated under the action of Al, Cr, and Ni elements to form a dense oxide film to prevent further corrosion and metal ion dissolution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 is the EDS element distribution spectrum of LCC-AHEA of the present invention; Figure 2 is the XRD pattern of LCC-AHEA of the present invention; Figure 3 The compression engineering stress-strain curves of LCC-AHEA and ordinary stainless steel in the present invention; Figure 4 The colony diagram of LCC-AHEA and common stainless steel in 100mL is shown; Figure 5 The Tafel curves of the LCC-AHEA of the present invention and common stainless steel in Hank's solution; Figure 6 This is the colony picture of LCC-AHEA of the present invention in PBS solution of Escherichia coli; Figure 7 A line graph showing the concentration of Al, Co, Cr, Cu and Ni ions of the LCC-AHEA of the present invention changing with time; Figure 8 This is a comparison chart of the yield strength and antibacterial rate of the LCC-AHEA of the present invention and other alloys. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0021] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] An antibacterial high entropy alloy with low copper content, the chemical formula of the antibacterial high entropy alloy is Al xCo y CrCu z FeNiSi 0.2 , where 0.3 ≤ x ≤ 0.6, 1.0 ≤ y ≤ 1.5, and 0.05 ≤ z ≤ 0.3.

[0023] The microstructure of the antibacterial high-entropy alloy is a two-phase structure, including a dendrite phase rich in Cr and Fe, and an interdendritic phase rich in Al and Ni. The ratio of the dendrite phase to the interdendritic phase is (7 ~ 8): (2 ~ 3).

[0024] The antibacterial high entropy alloy has better mechanical properties and corrosion resistance than traditional copper-containing stainless steel, copper-containing titanium alloy and ordinary antibacterial high entropy alloy due to the absence of copper-rich phase. The yield strength of the antibacterial high entropy alloy is 751 MPa, the ultimate compressive strain is 40% to 42%, and the passivation range is 0.5 V.

[0025] A passivation film is formed on the surface of the antibacterial high entropy alloy, which is destroyed under the condition of bacterial corrosion and continuously releases Al, Co, Cu, and Ni ions. The released ions synergistically destroy the morphological integrity of bacteria, inhibit bacterial division, and achieve high-efficiency antibacterial effect. In the absence of bacterial corrosion, no harmful ions are released to pollute the environment.

[0026] The high strength of this low-copper antibacterial high-entropy alloy comes from high lattice distortion and high-density phase boundaries. The high lattice distortion comes from the different atomic sizes that make up the LCC-AHEA (low-copper antibacterial high-entropy alloy) lattice. This lattice distortion introduces high-amplitude slip resistance, making plastic deformation difficult. The high-density phase boundaries can also directly hinder slip, allowing LCC-AHEA to withstand higher loads than ordinary stainless steel. At the same time, LCC-AHEA fails at a compressive engineering strain of about 41%, indicating that it has good plasticity, which is due to the coordinated deformation of the fine two-phase structure. In addition, another notable feature of the LCC-AHEA compressive stress-strain curve is its strong continuous strain hardening ability, with a hardening rate close to 5GPa. The reason is that dislocations accumulate at high-density phase boundaries, increasing the back stress and allowing LCC-AHEA to obtain additional strain hardening.

[0027] The antibacterial high entropy alloy with low copper content of the present invention draws on the design concept of high entropy alloys and utilizes the high entropy effect and cocktail effect of high entropy alloys to achieve good mechanical properties, corrosion resistance and antibacterial properties; by reducing the Cu element content and utilizing the synergistic antibacterial effect of multiple elements contained in the antibacterial high entropy alloy, strong antibacterial effect is achieved, which has the advantage of solving the shortcomings of insufficient corrosion resistance and mechanical properties of traditional antibacterial metal materials with high copper content, while achieving excellent antibacterial effect, forming an antibacterial high entropy alloy with excellent mechanical properties, antibacterial properties and corrosion resistance.

[0028] The antibacterial high entropy alloy with low copper content of the present invention has an antibacterial rate of 96% to 98% for Escherichia coli in one day and 100% for three days. Its antibacterial performance comes from the synergistic effect of Al, Ni, Cu and other ions led by Co, which replaces the high-content Cu element to achieve high-efficiency antibacterial. The specific process includes: the microbial corrosion of Escherichia coli destroys the dense oxide film on the surface of the alloy and releases Al, Co, Cu, Ni and other ions; these ions destroy the integrity of the Escherichia coli cell structure, interfere with its DNA replication and RNA transcription, and inhibit its division; after the death of Escherichia coli, the alloy surface is rapidly passivated under the action of Al, Cr, and Ni elements to form a dense oxide film to prevent further corrosion and metal ion dissolution.

[0029] Correspondingly, the present invention also provides a method for preparing the above-mentioned antibacterial high entropy alloy with low copper content, comprising the following steps: Step 1: Follow Al x Co y CrCu z FeNiSi 0.2 Ingredients: Each element uses high-purity bulk raw materials of Al, Co, Cr, Cu, Fe, Ni, and Si with a content of more than 99.9wt.%.

[0030] Step 2, subjecting the ingredients of step 1 to multiple suspension smelting in an oxygen-free environment to obtain a high entropy alloy ingot; The high-purity raw materials are added into the magnetic suspension melting furnace in sequence. The induction melting temperature is 1900 ~ 2100℃. At the same time, the furnace is vacuumed to 4 ~ 6×10 -3 Pa, and then backfill with high-purity argon gas to 0.03 ~ 0.05 MPa to create an oxygen-free melting environment; Melting is carried out in a vacuum magnetic levitation melting furnace to alloy the raw materials. Each alloy ingot is remelted at least four times to ensure the uniformity of chemistry and microstructure; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

[0031] The high entropy alloy ingot is forged and hot-rolled to form welding pores, so that the antibacterial high entropy alloy obtains a finer microstructure and an antibacterial high entropy alloy sheet is obtained.

[0032] Example 1 An antibacterial high entropy alloy with low copper content, the chemical formula of the antibacterial high entropy alloy is Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 .

[0033] The Al 0.3 Co1.2 CrCu 0.05 FeNiSi 0.2 The preparation method of antibacterial high entropy alloy is as follows: Step 1: According to the alloy composition Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 Ingredients: Step 2: Add high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni and Si into the magnetic suspension melting furnace in sequence, and perform vacuum melting in an oxygen-free environment. The vacuum melting method is as follows: First, evacuate the furnace to a vacuum of 4 × 10 -3 Pa, then, backfilling high-purity argon gas to 0.03MPa, adjusting the magnetic suspension melting furnace to an oxygen-free atmosphere; melting in a vacuum magnetic suspension melting furnace, the induction melting temperature is 1900°C, and the high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni, and Si are alloyed, and each alloy ingot is remelted at least four times to ensure the uniformity of chemistry and microstructure, and obtain a high-entropy alloy ingot; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

[0034] Example 2 An antibacterial high entropy alloy with low copper content, the chemical formula of the antibacterial high entropy alloy is Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 .

[0035] The Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 The preparation method of antibacterial high entropy alloy is as follows: Step 1: According to the alloy composition Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 Ingredients: Step 2: Add high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni and Si into the magnetic suspension melting furnace in sequence, and perform vacuum melting in an oxygen-free environment. The vacuum melting method is as follows: First, evacuate the furnace to a vacuum of 5 × 10 -3Pa, then, backfilling high-purity argon gas to 0.04MPa, adjusting the magnetic suspension melting furnace to an oxygen-free atmosphere; melting in a vacuum magnetic suspension melting furnace, the induction melting temperature is 2000°C, and the high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni, and Si are alloyed, and each alloy ingot is remelted at least four times to ensure the uniformity of chemistry and microstructure, and obtain a high-entropy alloy ingot; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

[0036] Example 3 An antibacterial high entropy alloy with low copper content, the chemical formula of the antibacterial high entropy alloy is Al 0.6 CoCrCu 0.1 FeNiSi 0.2 .

[0037] The Al 0.6 CoCrCu 0.1 FeNiSi 0.2 The preparation method of antibacterial high entropy alloy is as follows: Step 1: According to the alloy composition Al 0.3 Co 1.2 CrCu 0.05 FeNiSi 0.2 Ingredients: Step 2: Add high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni and Si into the magnetic suspension melting furnace in sequence, and perform vacuum melting in an oxygen-free environment. The vacuum melting method is as follows: First, evacuate the furnace to a vacuum of 5 × 10 -3 Pa, then, backfilling high-purity argon gas to 0.04MPa, adjusting the magnetic suspension melting furnace to an oxygen-free atmosphere; melting in a vacuum magnetic suspension melting furnace, the induction melting temperature is 2000°C, and the high-purity raw materials of A1, Co, Cr, Cu, Fe, Ni, and Si are alloyed, and each alloy ingot is remelted at least four times to ensure the uniformity of chemistry and microstructure, and obtain a high-entropy alloy ingot; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

[0038] Step 4: Cut the low copper content antibacterial high entropy alloy into 100×100×10 mm 3 The cylindrical specimen and sheet specimen are processed by wire cutting. The size of the cylindrical specimen is φ4mm×6mm, and the size of the sheet specimen is 9mm×9mm×2mm.

[0039] See also Figure 1 ~ Figure 8In order to study the anisotropy of LCC-AHEA, columnar specimens and sheet specimens were sampled in the rolling direction and normal direction, respectively. The columnar specimen in the rolling direction was defined as a columnar specimen with an axis parallel to the rolling direction, the columnar specimen in the rolling normal direction was defined as a columnar specimen with an axis parallel to the rolling normal direction, the sheet specimen in the rolling direction was defined as a sheet specimen with a main surface normal parallel to the rolling normal direction, and the sheet specimen in the rolling normal direction was defined as a sheet specimen with a main surface normal parallel to the rolling normal direction. In addition, columnar specimens and sheet specimens of 3Cr13 stainless steel, 440C stainless steel, Al, Co, Cr, Cu, and Ni of the same size were selected for comparison. In the present invention, 3Cr13 stainless steel and 440C stainless steel are collectively referred to as ordinary stainless steel, and Al, Co, Cr, Cu, and Ni are collectively referred to as pure metals.

[0040] Figure 1 The EDS element distribution spectrum of LCC-AHEA prepared in Example 3; Figure 2 XRD pattern of LCC-AHEA prepared in Example 3; Figure 3 The compressive engineering stress-strain curves of LCC-AHEA prepared in Example 3 and ordinary stainless steel; Figure 4 The LCC-AHEA prepared in Example 3 and ordinary stainless steel were mixed in 100 mL containing 10 5 CFU / mL Escherichia coli in PBS solution, after immersion for 1, 3, and 7 days, the colony was coated with 100 μL of 100-fold diluted bacterial solution; Figure 5 The Tafel curves of LCC-AHEA prepared in Example 3 and ordinary stainless steel in Hank's solution; Figure 6 The pure metal raw materials used for preparing LCC-AHEA in Example 3 include pure Al, Co, Cr, Ni, and Cu flakes, and 100 mL of the raw materials contain 10 5 CFU / mL Escherichia coli in PBS solution, after immersion for 1, 3, and 7 days, the colony was coated with 100 μL of 100-fold diluted bacterial solution; Figure 7 A line graph showing the concentration of Co and Cu ions in the LCC-AHEA prepared in Example 3 in the E. coli solution and the sterile PBS solution over time; Figure 8 Comparison of the yield strength and antibacterial rate of LCC-AHEA prepared in Example 3 with other alloys of the same type.

[0041] SEM and EDS characterization of S100 and LCC-AHEA.

[0042] The LCC-AHEA flake sample was ground flat with 2000# sandpaper and then polished with 0.03μm diamond suspension. The SE and EDS images of the LCC-AHEA flake sample were taken using a scanning electron microscope (Sigma 500, Zeiss, Germany) equipped with an energy dispersive spectrometer (EDS) to analyze the microstructure and element distribution, with an accelerating voltage of 30kV. The SEM results are shown in Figure 2. Figure 1 As shown in Figure 2, the microstructure of LCC-AHEA is composed of two phases: dendrites rich in Cr and Fe (about 80%) and interdendritic phases rich in Al and Ni (about 20%).

[0043] XRD characterization of S200 and LCC-AHEA For the LCC-AHEA flake sample, the crystal structure of the LCC-AHEA flake sample was analyzed by X-ray diffraction (XRD) using a Bruker-D8 Advance instrument. The target material used was Cu, the diffraction angle 2θ range was 5°~80°, the scanning step was 0.02°, and the scanning speed was 4.86° / min. The XRD results are shown in Figure 2. Figure 2 As shown, the crystal structure of LCC-AHEA is FCC with a lattice constant of 3.59 Å.

[0044] Mechanical properties test of S300, LCC-AHEA and ordinary stainless steel The room temperature compression performance of the prepared LCC-AHEA and ordinary stainless steel cylindrical specimens was tested using a UTM-5105 testing machine at a strain rate of 1×10 −3 s −1 The mechanical properties test results are as follows: Figure 3 As shown, the yield strength of LCC-AHEA is about 751 MPa, and there is no significant difference between the rolling direction and the rolling normal direction.

[0045] Antibacterial performance test of S400, LCC-AHEA and ordinary stainless steel.

[0046] The antibacterial properties of LCC-AHEA and ordinary stainless steel sheet specimens were studied using the coating counting method.

[0047] The LCC-AHEA sheet specimens in the rolling direction, the LCC-AHEA sheet specimens in the rolling normal direction, the 440C sheet specimens, and the 3Cr13 sheet specimens were placed in their respective conical flasks, while the blank control flask did not contain the metal flakes. Subsequently, they were sterilized in an autoclave at 121°C for 20 minutes and dried to eliminate moisture. The E. coli suspension was diluted to 10 5 CFU mL -1 The concentration of 10 is 100mL. 5 CFU mL-1 The bacterial suspension was poured into a conical flask, and 100 mL of the bacterial suspension was aliquoted and inoculated into the corresponding conical flasks, and cultured in a 37°C shaker for 1, 3, and 7 days. At each time point, 100 μL of the bacterial suspension diluted 100 times was taken and spread on a nutrient agar plate. After culturing at 37°C for 24 hours, the number of colonies was counted. The antibacterial rate was determined by the following formula:

[0048] in, and Represents the number of colonies obtained on the coated plate in the experimental group and the control group respectively. Figure 4 As shown in the figure, the antibacterial rate of LCC-AHEA was about 96% to 98% in one day, and 100% antibacterial rate was achieved in three days, with no significant difference between the rolling direction and the rolling normal direction.

[0049] Corrosion resistance test of S500, LCC-AHEA and ordinary stainless steel The corrosion resistance of the LCC-AHEA prepared in step 1 and ordinary stainless steel sheet samples was studied using a CHI660e electrochemical analyzer. During the corrosion resistance test, the sample was used as the working electrode (WE), platinum foil as the counter electrode (CE), and saturated calomel as the reference electrode (RE). After the open circuit potential (OCP) test for 30 min, the sample was immersed in a balanced salt solution at 37°C for testing. The potential range was -0.5 V ~ +1.5 V, and the scanning rate was 0.001 V / s to obtain the Tafel curve. Figure 5 As shown, it was found that LCC-AHEA has a passivation range of nearly 0.5V, while 440C and 3Cr13 are less than 0.2V, indicating that a dense oxide film can be quickly formed on the surface of LCC-AHEA to resist external corrosion.

[0050] Antibacterial performance test of S600, Al, Co, Cr, Cu and Ni Metal sheets of Al, Co, Cr, Cu, and Ni (purity>99.999%) of the same size as S300 were selected and the coating counting analysis was performed under the same conditions as step 5. The results are shown in step 6. Co, Ni, and Cu elements showed good antibacterial effects, Ni element had a general antibacterial effect, and Cr seemed to promote the growth of E. coli.

[0051] Dissolution ion concentration of S700 and LCC-AHEA in bacterial solution ICP-MS (Agilent 7700, Agilent, America) was used to detect the ion concentrations in the bacterial solution of S300 and the extract of LCC-AHEA immersed in sterile PBS. 10 mL of bacterial solution was selected and tested directly without dilution. The results are shown in Figure 2. Figure 7 As shown in the figure, it was found that the ion concentrations of Al, Co, Cr, Ni, and Cu in the sterile PBS extract slowly increased and were basically saturated on the 1st and 2nd days, and the saturated ion concentration was less than 25 μg / L. In contrast, the ion concentrations of Al, Co, Cr, and Ni in the bacterial solution increased almost linearly over time, and the ion concentrations on the 7th day were around 185 μg / L, 230 μg / L, 145 μg / L, and 210 μg / L, respectively. The ion dissolution rate was nearly 20 times that of the metal extract, and there was no obvious saturation trend.

[0052] Discussion on the antibacterial mechanism of S800 and LCC-AHEA Although Figure 6 The Cu plate in LCC-AHEA has an antibacterial rate of 100%, but the Cu content in LCC-AHEA is lower than (wt. 2.5%), and the concentration of ion dissolution is much lower than that of the same type of antibacterial alloys. Therefore, the Cu element is not considered to be the main source of the antibacterial effect of LCC-AHEA. In view of the strong antibacterial effect of Co and the high concentration of ion dissolution, the Co element should be the main source of the antibacterial properties of LCC-AHEA. Al and Ni elements have certain antibacterial effects. Therefore, the antibacterial performance of LCC-AHEA is believed to come from the synergistic effect of Al, Ni, Cu and other ions led by Co, thereby replacing the high content of Cu elements to achieve high-efficiency antibacterial, which is a manifestation of the cocktail effect of high-entropy alloys.

[0053] Comparison of yield strength and antibacterial properties of S900, LCC-AHEA and existing similar materials. like Figure 8 As shown in the figure, by comparing the comprehensive performance of LCC-AHEA with existing antibacterial alloys, it is found that the antibacterial performance and strength of the LCC-AHEA developed in this study are much higher than those of copper-containing stainless steel, copper-containing titanium alloy and ordinary AHEA, and it is a high-quality AHEA.

[0054] This antibacterial high entropy alloy with low copper content has obtained excellent mechanical properties and antibacterial properties that surpass existing antibacterial alloys. Secondly, the antibacterial high entropy alloy has long-lasting antibacterial properties. When there is bacterial corrosion, it can release Al, Co, Cu, Ni and other ions, and can continue to be antibacterial in the service environment. In addition, the antibacterial high entropy alloy has excellent corrosion resistance and can resist the erosion of salt solutions such as tissue fluid and seawater. When there is no bacterial corrosion, a dense oxide film is quickly formed on the surface to prevent the release of harmful ions.

[0055] Example 4 The invention discloses an antibacterial high entropy alloy with low copper content and its application in the field of antibacterial metal materials.

[0056] The field of antibacterial metal materials includes food processing, home furnishing, medical equipment and major national protective engineering equipment.

[0057] The antibacterial high entropy alloy inhibits the life activities of E. coli mainly through the dissolution of metal ions. The specific process is as follows: First, the MIC effect of E. coli can destroy the dense oxide film on the surface of LCC-AHEA, corrode the metal itself, and continuously release Al, Co, Cu, Ni and other ions. Second, the continuously dissolved Al, Co, Ni, Cu and other ions destroy the integrity of the morphology of E. coli, and the morphology gradually becomes concave and wrinkled, and enters the cell to interfere with DNA replication and RNA transcription, making it impossible for E. coli to secrete extracellular proteins and proliferate, but E. coli will not be killed immediately, and can still carry out some life activities including MIC; Third, after the death of E. coli, with the help of Al, Cr, and Ni elements, the surface of LCC-AHEA can be quickly passivated to form a dense oxide film to resist the erosion of PBS solution, inhibit the dissolution of metal ions, and avoid excessive pollution to the external environment. The ion concentration of Cu element in both bacterial solution and extract was less than 25 μg / L, which was much lower than the effective antibacterial concentration of Cu ions. This indicated that the antibacterial effect of LCC-AHEA was not entirely derived from the traditional antibacterial effect of Cu ions, but from the combined effect of metal ions such as Al, Ni, and Cu, led by Co ions.

[0058] The antibacterial high entropy alloy uses the high entropy effect and cocktail effect of high entropy alloy to achieve good mechanical properties, corrosion resistance and antibacterial properties. The synergistic antibacterial effect of multiple elements contained in the antibacterial high entropy alloy achieves strong antibacterial properties, solves the shortcomings of traditional antibacterial metal materials with high copper content, such as insufficient corrosion resistance and mechanical properties, and obtains excellent antibacterial effects; the alloy can not only meet the antibacterial performance requirements of metal materials used in fields such as food processing, household and medical equipment, but is also expected to be used in major national protective engineering equipment such as cross-sea bridges, deep-sea buried pipelines, aircraft carriers, and biomedical antiviral equipment.

[0059] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. An antibacterial high entropy alloy with low copper content, characterized in that: The chemical formula of the antibacterial high entropy alloy is Al x Co y CrCu z FeNiSi 0.2 , where 0.3 ≤ x ≤ 0.6, 1.0 ≤ y ≤ 1.5, and 0.05 ≤ z ≤ 0.

3.

2. The antibacterial high entropy alloy with low copper content according to claim 1, characterized in that: The microstructure of the antibacterial high entropy alloy is a two-phase structure, including a dendrite phase rich in Cr and Fe, and an interdendritic phase rich in Al and Ni.

3. The antibacterial high entropy alloy with low copper content according to claim 2, characterized in that: The ratio of the dendrite phase to the interdendritic phase is (7 to 8): (2 to 3).

4. The antibacterial high entropy alloy with low copper content according to claim 1, characterized in that: A passivation film can be formed on the surface of the antibacterial high entropy alloy, which is destroyed under the condition of bacterial corrosion and continuously releases Al, Co, Cu, and Ni ions. The released ions synergistically destroy the morphological integrity of bacteria, inhibit bacterial division, and achieve antibacterial effect.

5. The antibacterial high entropy alloy with low copper content according to claim 1, characterized in that: The antibacterial high entropy alloy has a yield strength of 751 MPa, an ultimate compressive strain of 40% to 42%, and a passivation interval of 0.5 V.

6. The antibacterial high entropy alloy with low copper content according to claim 1, characterized in that: The antibacterial rate of the antibacterial high entropy alloy against Escherichia coli is 96% to 98% in one day and 100% in three days.

7. A method for preparing an antibacterial high entropy alloy with low copper content according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Follow Al x Co y CrCu z FeNiSi 0.2 Ingredients: Step 2, subjecting the ingredients of step 1 to multiple vacuum suspension melting in an oxygen-free environment to obtain a high entropy alloy ingot; Step 3: Forging and hot rolling the high entropy alloy ingot to obtain an antibacterial high entropy alloy with a low copper content.

8. The method for preparing an antibacterial high entropy alloy with low copper content according to claim 7, characterized in that: The temperature of the suspension smelting in step 2 is 1900-2100°C.

9. The method for preparing an antibacterial high entropy alloy with low copper content according to claim 7, characterized in that: The vacuum degree is 4 ~ 6×10 -3 Pa, and then the vacuum chamber is backfilled with high-purity argon gas to 0.03 ~ 0.05 MPa to form an oxygen-free melting environment.

10. Application of an antibacterial high entropy alloy with low copper content in the field of antibacterial metal materials.